TARGETED SUB-COLLECTION OF POTATO CULTIVARS SPECIFIC TO LATE BLIGHT RESISTANCE - L. I. Kostina; O. S. Kosareva (Труды по прикладной ботанике, генетике и селекции)
Background. The article presents the data obtained after the screening of potato cultivars for resistance to Phytophthora infestans (Mont.) de Bary. The selected genotypes combine late blight resistance with other valuable commercial traits, such as high yield, high starch content, resistance to virus diseases and potato nematode (Globodera rostochiensis Woll.).Materials and methods. Potato accessions representing domestic and foreign cultivars from the VIR collection served as the material for this research. The screening was performed according to the techniques developed at the Potato Genetic Resources Department of VIR.Results and conclusion. The following true-breeding cultivars were identified for their resistance to Phytophthora infestans: ‘Ania’ (k-24063), ‘Baszta’ (k-24067), ‘Bobr’ (k-21103), ‘Dunajec’ (k-24074), ‘Klepa’ (k-24080), ‘Koga’ (k-24174), ‘Meduza’ (k-24082) and ’Mors’ (k-24083) from Poland; ‘Caprice’ (k-25193), ‘Certo’ (k-19440) and ‘Valetta’ (k-21769) from Germany; ‘Avrora’ (k-12188), ‘Bastion’ (k-25198), ‘Bryansky nadezhny’ (k-12160), ‘Vdokhnoveniye’ (k-12192), ‘Vektor’ (k-25200), ‘Velikan’ (k-25201), ‘Zvezdochka’ (к-25209), ‘Kalinka’ (k-25148), ‘Lukyanovsky’ (k-11750), ‘Musinsky’ (k-25312), ‘Nakra’ (k-11916), ‘Nikulinsky’ (k-12171), ‘Prizer’ (k-25217), ‘Rapsodiya’ (k-25258), ‘Rossiyanka’ (k-12057), ‘Rucheyek’ (k-12213) and ‘Udacha’ (k-11900) from Russia; ‘Aktsent’ (k-12237), ‘Vetraz’ (k-11989), ‘Vytok’ (k-11897), ‘Zhuravinka’ (k-12106), ‘Kupalinka’ (k-12155), ‘Sintez’ (k-11666), ‘Suzorye’ (k-11992) from Belarus; ‘Vikhola’ (k-11270), ‘Zarevo’ (k-10773), ‘Svitanok kievsky’ (k-11665), ‘Olviya’ (k-25094), ‘Rakurs’ (k-25098) from Ukraine; ‘Aytmurat’ (k-25248), ‘Berkut’ (k-25250), ‘Zholbarys’ (k-25155), ‘Nur-Alem’ (k-25253), ‘Senim’ (k-25306), ‘Seyanets Lapteva’ (k-25161), ‘Sunkar’ (k-25258), ‘Tamyz’ (k-25307) and ‘Udovitsky’ (k-25260) from Kazakhstan; etc. High percentage of plantlets resistant to late blight was observed among self-pollination progenies of cvs. ‘Avrora’ (k-12188), ‘Astra’ (k-10697), ‘Vikhola’ (k-11270), ‘Zhuravinka’ (k-12106), ‘Nayada’ (k-12157), ‘Rosinka’ (k-11993), ‘Skarb’ (k-11904), ‘Bobr‘ (k-21103) and ‘Clarissa’ (k-21770). There were cultivars combining late blight resistance with such traits as resistance to potato nematode (Globodera rostochiensis Woll.) and viruses, high productivity, and increased starch content: ‘Zhuravinka’, ‘Ania’, ‘Baszta’, ‘Bobr’, ‘Certo’ and ‘Mors’. The selected genotypes are recommended as promising to be included in potato breeding programs.